Being Chinese, becoming Chinese American - Chen, Shehong, 1954- (Asian American experience., 2002)
"In this foundational study, Shehong Chen investigates how Chinese immigrants to the United States transformed themselves into Chinese Americans during the crucial period between 1911 and 1927"--Jacket.